Analisis Peran Testimoni dan Kyualitas Pelayanan Terhadap Keputusan Pembelian Mie Gacoan di Garut - Hilman Rismanto; Aulia Agustina; Asep Kuswendi; Firdan Rustandi; Sandi Mustapa (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to empirically analyze the effect of testimonials and service quality on purchasing decisions at Mie Gacoan in Garut. This study was prompted by the phenomenon of high consumer visits despite many negative reviews regarding service speed and waiting times. This study uses an explanatory survey method with a quantitative approach. Data were collected through an online questionnaire distributed to 100 respondents selected using purposive sampling techniques. The data analysis method applied was multiple linear regression, preceded by classical assumption tests and hypothesis testing using t-tests and F-tests. The results show that testimonials do not have a significant effect on purchasing decisions, with a contribution of 0.1%, while service quality also does not have a significant effect with a contribution of 1.2%. Concurrently, both variables did not significantly influence purchasing decisions, with an R Square value of 0.013. These findings suggest that Mie Gacoan consumers' purchasing decisions in Garut are more influenced by factors outside the research model, such as price perception and product taste. This study implies that in the low- cost fast food industry, brand popularity and price advantage may be more dominant than the influence of service quality and digital testimonials.